PENGEMBANGAN SUNGAI BANJIR KANAL TIMUR SEMARANG SEBAGAI TRANSPORTASI SUNGAI UNTUK TUJUAN WISATA - Amar Ma'rruf; Adik Satya Graha; Salamun Salamun; Ismiyati Ismiyati (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Tourism is a sector that can potentially be developed to finance local expenditure. Especially Semarang City Government, actively prosecuted in tourism development with the potential to manage objects in the city of Semarang. Old City is one of the attractions that are less optimized, so that the East Canal Flood Basin Development Semarang can increase tourism demand in the Old City is the transport stream that is integrated with the shuttle bus in the Old City. The purpose of this study was to analyze the East Flood Canal apart as if the flood control can also be used as the transport stream as the water tourist destination in the city of Semarang. Methodology used in the study of development of River Flood Canal Tmur Semarang As river transport to destination covering methods of qualitative and quantitative methods. Qualitative method with a questionnaire to determine the potential demand in the Old Town, while the quantitative method with HEC-RAS program to analyze hydrological and determine discharge plans. Ouput obtained from this study is the use of river tourism speedboat 8 m 2 open with 8 m long, 2.2 m wide and 0.4 m draft and is integrated with the shuttle bus pick-up two levels. Ship Operating Costs amounted to Rp 1,052,717,443,-/year for a fee ranging from investments to cost management and management with 8 times the trip in one day. Rates are charged per passenger Rp 18 208, - for a one-way trip.